Development of a Transparent Scratch Resistant Coating through Direct Oxidation of Al‐Coated Glass1 . Issue 1 (19th October 2016) - Mousavi, Sayed Hadi; Jilavi, Mohammad Hossein; Koch, Marcus; Arzt, Eduard; de Oliveira, Peter William
Abstract : The authors develop a protective transparent coating of aluminum oxide through direct oxidation of aluminum‐coated glass. Aluminum coatings are deposited on low‐iron glass substrates using a physical deposition method and then oxidized at different temperatures. A uniform nano‐porous structure with grain sizes of approximately 30–80 nm is observed. X‐ray diffraction, TEM images, and EDX analysis indicate the formation of crystalline γ‐Al2 O3, Si, and stishovite‐SiO2 as a result of interdiffusion. The samples treated at different temperatures have hardness values ranging from 5 to 9 H, which is within the desirable range for industrial scratch‐resistant coatings. The optical transmission of around 75–85% at visible wavelengths makes the proposed technique useful for the design of protective transparent coatings. Abstract : Scratch ‐resistant thin films of aluminum oxide are developed through a simple and cost‐effective sputtering method. The fabricated layers are composed of aluminum oxide, silicon, and silicon dioxide which play an important role in the high scratch resistance and lead to acceptable transmission. The development of protective transparent layers may find different applications in display and glass industry.